In utero exposure to diesel exhaust particulates is associated with an altered cardiac transcriptional response to transverse aortic constriction and altered DNA methylation. Issue 11 (27th July 2017) - Goodson, Jamie M.; Weldy, Chad S.; MacDonald, James W.; Liu, Yonggang; Bammler, Theo K.; Chien, Wei‐Ming; Chin, Michael T.
Abstract : In utero exposure to diesel exhaust air pollution has been associated with increased adult susceptibility to heart failure in mice, but the mechanisms by which this exposure promotes susceptibility to heart failure are poorly understood. To identify the potential transcriptional effects that mediate this susceptibility, we have performed RNA sequencing analysis on adult hearts from mice that were exposed to diesel exhaust in utero and that have subsequently undergone transverse aortic constriction. We identified 3 target genes, Mir133a‐2, Ptprf, and Pamr1, which demonstrate dysregulation after exposure and aortic constriction. Examination of expression patterns in human heart tissues indicates a correlation between expression and heart failure. We subsequently assessed DNA methylation modifications at these candidate loci in neonatal cultured cardiac myocytes after in utero exposure to diesel exhaust and found that the promoter for Mir133a‐2 is differentially methylated. These target genes in the heart are the first genes to be identified that likely play an important role in mediating adult sensitivity to heart failure. We have also shown a change in DNA methylation within cardiomyocytes as a result of in utero exposure to diesel exhaust.—Goodson, J. M., Weldy, C. S., MacDonald, J. W., Liu, Y., Bammler, T. K., Chien, W.‐M., Chin, M. T. In utero exposure to diesel exhaust particulates is associated with an altered cardiac transcriptional response to transverse aortic constriction and altered DNA methylation. FASEB J. 31, 4935–4945 (2017). www.fasebj.org